The Perspectives on Consumer Attitudes and Actions: The Impact of Political and Social Factors on the Pro-Israel Products Boycott Movement (Case Study in Indonesia): Perspektif Sikap dan Tindakan Konsumen: Dampak Faktor Politik dan Sosial terhadap Gerakan Boikot Produk Pro-Israel (Studi Kasus di Indonesia) - Pasryb, Andi Syahida Ulhaq; Munir, Abdul Razak; Aswan, Andi; Balele, Andi Bintang (AMAR (Andalas Management Review), 2024)
This study explores the extent to which political and social factors drive consumer participation in the boycott movement against Pro-Israel products in Indonesia, using a qualitative research approach. Data were collected through an online survey involving 65 respondents, focusing on their awareness, motivations, actions, and perceptions regarding the boycott. The results indicate a high level of awareness and active participation, with 100% of respondents engaging in the boycott movement. Ethical considerations, particularly concerns over human rights (60%) and personal values (40%), were identified as the primary motivators. While half of the participants believed that boycotting is an effective way to influence political decisions, a significant portion remained neutral, highlighting some uncertainty about the impact of such actions. The study also reveals that a company's stance on political issues significantly affects consumer perceptions, with 60% of respondents viewing brands that support the boycott more positively. Additionally, 50% of participants expressed a willingness to pay a premium for products not associated with Israel. These findings suggest a growing trend toward value-based consumerism, where political and social factors heavily influence purchasing decisions. The research concludes that businesses must adapt to this shift by aligning with ethical and socially responsible practices to maintain positive brand perception and consumer loyalty. This study contributes to a deeper understanding of how political and social factors shape consumer behavior and the implications for corporate strategies in a global context.